Challenging Nation-Statism: Political Boundaries and Bodies at the Border - Kaul, Nitasha (ACME, 2023)
Critical scholarship can be a way of enacting insurrections against entrenched and enduring dogmatisms of the nation-state and its inalienable right to systematically deploy violence against selective Others. This article focuses upon the violent bordering practices of the nation-statist system, their connexion to the bordering of knowledges, and their impact upon specific kinds of bodies at the border, which together enforce a systemic vulnerability that is tied to legacies of colonialism, slavery, and capitalism. In the first part, I reflect upon the violence of bordering practices in the nation-statist system, foregrounding how those who predominantly receive this violence in the form of death and debility are the racialized Others. I put forth four specific implications of these violent bordering practices: they enable a cascade of interlinked dehumanizations of people within the nation-state borders; they occlude from view how any nation-state is not homogeneous over time in terms of what one might see as national culture; they allow economic processes to be perceived as scientific and abstract rather than as embedded in the realms of contested political jurisdictions; and they render and sustain the nation-state itself as a racialized construct that both produces and profits from class inequality in contemporary capitalism. In the second part, I argue for the need to perceive the link between violent bordering practices and bordered knowledges, highlighting and synthesizing insights from across disciplines that can aid in asking counter-hegemonic questions. In conclusion, and as part of necessary anti-national scholarly enquiry, I call for a multidimensional and sustained critical stance towards the nation-states’ rights to enforce borders.